Evaluasi Pelayanan Angkutan Penyeberangan Pada KMP.Siginjai Lintasan Jepara “Karimunjawa Provinsi Jawa Tengah - Eko Nugroho Widjatmoko; Andri Yulianto; Siti Nurlaili Triwahyuni; Hadisty Ciptawardhani (Syntax Idea)
Jepara Ferry Port is located in Jepara Regency, Central Java Province. The Jepara Ferry Port has three vessels in operation, namely KMP.Siginjai, KMC.Express Bahari 1C and KMC.Express Bahari 3F. There are several services that do not comply with regulations and are carried out by ship operators, even though the services on board have been regulated by the government to provide a sense of security and comfort during the crossing. This research aims to determine the level of suitability of ferry transportation services at KMP. Siginjai on the current conditions regarding Minimum Service Standards and knowing the service attributes that need to be improved on a priority scale. The method used is analysis of the level of suitability of SPM for ferry transportation and IPA to determine service attributes that need to be improved on a priority scale. Based on the results of the analysis and calculations, it was found that KMP.Siginjai had a suitability level for passenger services, namely 69.35%, KMP.Siginjai vehicle loading services, namely 75%, ship operation services, namely 100% and the results obtained were that service attributes needed to be improved on a priority scale for aspects Passenger services include first aid kits which are not yet available, security officers, reclining seats and sofas, separate toilets and passenger baggage facilities. In vehicle loading services, the attributes on the priority scale are evacuation routes, distance between vehicles and the distance between the ship wall and the vehicle and a light intensity of 200 – 300 Lux. The strategy offered to increase comfort and satisfaction is to provide facilities that are located on a priority scale.